Infection control procedures used by Paraguayan dentists to reduce biological risk in dental practice during the Covid-19 pandemic - Díaz-Reissner, Clarisse Virginia; Adorno, Carlos Gabriel; Cataldi-López, Leticia; Fretes-López, Vicente Reinaldo; Ballasch, Gabriela Rosmary; Jara-Pintos, Cynthia Mireya (Revista Facultad de Odontología Universidad de Antioquia, 2021)
Introduction: dental professionals have been identified as having a very high risk of exposure to coronavirus, specifically when they carry out procedures to generate aerosols in infectious patients. The objective was identifying the mechanical and chemical mechanisms used by Paraguayan dentists to prevent the spread of COVID-19. Evaluate the percentage of dentists who have treated positive COVID patients and who have subsequently developed the disease. Methods: it was a crosssectional descriptive observational study. Paraguayan dentists with internet access participated. The questions were about sociodemographic data and protection measures used in the office to reduce biological risk. The access link was disseminated through social networks. Results: 428 dentists participated in the study, 84.11 % were women, 38.32 % were 30-39 years old. The most used disinfection and care measures were dental chair disinfection (96.7 %), hand washing (93.46 %) and surface disinfection with alcohol 70 (88.08 %). 59.1% used 1% hydrogen peroxide as a preoperative mouthwash. The majority wore KN95 masks (48.83 %), woven cloth robe (78.04 %), disposable robe (72.20 %); The patient is fitted with a disposable surgeon’s cap (89.49 %) and/or shoe covers (76.40 %), and their instruments are sterilized in an autoclave (82.48 %). One professional reported having been infected in the dental office. Conclusion: most of the Paraguayan dentists surveyed comply with the protocols established by the Ministry of Health and international organizations, which appear to be effective as protection mechanisms against COVID-19 in the clinical environment.